Sudden cardiac death - a known unknown? - Obrova, Jana; Sovova, Eliska; Kocianova, Eva; Taborsky, Milos (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2022)
Sudden cardiac death (SCD) is a major medical, economic and social problem. The estimated annual number of SCDs is approximately 4 million cases worldwide. Approximately 50% of SCDs are unexpected first manifestations of cardiac disease. The survival rate after out-of-hospital cardiac arrest is low even in countries with the most advanced health care systems. It all emphasizes the importance of prevention, in which implantable cardioverter-defibrillators play a dominant role. However, our ability to recognize high-risk patients remains insufficient. Moreover, a declining rate of shockable rhythm as the initial recording has been reported in the last decades. Despite numerous SCD studies and undisputed progress, there are still many unanswered questions.
Keywords: mechanism; Death, Sudden, Cardiac; Out-of-Hospital Cardiac Arrest; prevention; Humans; lidé; náhlá srdeční smrt; Survival Rate; risk stratification; sudden cardiac death; Defibrillators, Implantable; defibrilátory implantabilní; zástava srdce mimo nemocnici; míra přežití; implantable cardioverter-defibrillator